2018 48th European Microwave Conference (EuMC) 2018
DOI: 10.23919/eumc.2018.8541763
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Shaped-Beam Reflectarray Design Using Machine Learning Techniques

Abstract: This papers introduces the use of machine learning techniques for an efficient design of shaped-beam reflectarrays considerably accelerating the overall process while providing accurate results. The technique is based on the use of Support Vector Machines (SVMs) for the characterization of the reflection coefficient matrix, which provides an efficient way for deriving the scattering parameters associated with the unit cell dimensions. In this way, the SVMs are used within the design process to obtain a reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For example, NNs were used by Shan et al [203] to forecast the phase-shift, whereas kriging was suggested to forecast the electromagnetic response of reflectarray components [204] . Support vector regression (SVR) has been used to accelerate the examination [205] and to directly optimize narrowband reflectarrays [206] . To hasten calculations without reducing their precision, Prado et al [207] proposed a wideband SVR-based reflectarray design method, and demonstrated its ability to obtain wideband, dual-linear polarized, and shapedbeam reflectarrays for direct broadcast satellite applications.…”
Section: Heat Source Layout Designmentioning
confidence: 99%
“…For example, NNs were used by Shan et al [203] to forecast the phase-shift, whereas kriging was suggested to forecast the electromagnetic response of reflectarray components [204] . Support vector regression (SVR) has been used to accelerate the examination [205] and to directly optimize narrowband reflectarrays [206] . To hasten calculations without reducing their precision, Prado et al [207] proposed a wideband SVR-based reflectarray design method, and demonstrated its ability to obtain wideband, dual-linear polarized, and shapedbeam reflectarrays for direct broadcast satellite applications.…”
Section: Heat Source Layout Designmentioning
confidence: 99%